Involvement of Pneumocystis jirovecii in infectious and other diseases in children and adults with immunosuppression of various origin - Rybalkina T.N.; Karazhas N.V.; Kornienko M.N.; Avetisyan L.R.; Boshyan R.E.; Pulnova N.L.; Kabikova O.F.; Ivanova M.Yu.; Chereshneva E.V. (Клиническая микробиология и антимикробная химиотерапия)
Objective.